Chemical Composition of PM2.5 in Wood Fire and LPG Cookstove Homes of Nepali Brick Workers - Johnston, James D.; Beard, John D.; Montague, Emma J.; Sanjel, Seshananda; Lu, James H.; McBride, Haley; Weber, Frank X.; Chartier, Ryan T. (Atmosphere, 2021)
Household air pollution is a major cause of morbidity and mortality worldwide, largely due to particles ≤ 2.5 µm (PM2.5). The toxicity of PM2.5, however, depends on its physical properties and chemical composition. In this cross-sectional study, we compared the chemical composition of PM2.5 in brick workers’ homes (n = 16) based on use of wood cooking fire or liquefied petroleum gas (LPG) cookstoves. We collected samples using RTI International particulate matter (PM) exposure monitors (MicroPEMs). We analyzed filters for 33 elements using energy-dispersive X-ray fluorescence and, for black (BC) and brown carbon (BrC), integrating sphere optical transmittance. Wood fire homes had significantly higher concentrations of BC (349 µg/m3) than LPG homes (6.27 µg/m3, p < 0.0001) or outdoor air (5.36 µg/m3, p = 0.002). Indoor chlorine in wood fire homes averaged 5.86 µg/m3, which was approximately 34 times the average level in LPG homes (0.17 µg/m3, p = 0.0006). Similarly, potassium in wood fire homes (4.17 µg/m3) was approximately four times the level in LPG homes (0.98 µg/m3, p = 0.001). In all locations, we found aluminum, calcium, copper, iron, silicon, and titanium in concentrations exceeding those shown to cause respiratory effects in other studies. Our findings suggest the need for multi-faceted interventions to improve air quality for brick workers in Nepal.